Susceptibility in a Coupled Double Quantum Dot-Metal Nanoparticle System under Standing Wave Field - Akram, Haneen; Muwaffaq Abdullah; El Mustapha Feddi; Amin H. Al-Khursan; Ali M. Muslim (University of Thi-Qar Journal of Science, 2024)
The main purpose of this work is studying the linear Susceptibility in the hybrid nanostructure that composed of a dual quantum dot (DQD) and metal nanoparticle (MNP) hybrid system under a standing-wave field. In our model, we used density matrix equations by taking into our account the interaction between excitons and surface plasmons. The proposed DQD is composed of two QDs. Each QD contains an InAs QD with a disk shape. The interaction between the QD and the wetting layer (WL) is taken into consideration. The application of the standing wave field on DQD-MNP hybrid system was modeled and examined. The susceptibility of thehybridDQD-MNPsystem reduced by the pump field under a standing-wave field. The high susceptibility obtained with a wide MNP radius. An interesting result was shown in the inversion of the grating period with the tunneling component in the conduction band. The smaller size of DQD gave us high susceptibility due to the quantization effect.